When Gender Equality Policies in Practice Matter
XXII, 241 p. 16 illus.
Keywords: "When Gender Equality Policies in Practice Matter" explores the implementation process in equality politics. In a pathbreaking, within-country comparison the authors and editors use the GEPP approach to analyze gender equality policy implementation across seven sectors in France. The result is a triumph of systematic comparison that is essential reading for anyone interested in the analysis of gender policy implementation. Joni Lovenduski, Birkbeck, University of London This compelling book by leading authorities in the field advances our knowledge of why, how, and when putting gender equality policies into practice matters for achieving gender transformation. The systematic cross-sectoral study of France immerses the reader into the fascinating and messy process of gender equality policy implementation, providing a solid analytical framework as well as novel, surprising findings that will captivate scholars of political science, sociology, and gender and politics. Emanuela Lombardo, Madrid Complutense University, Spain This book analyses gender equality policy implementation in France. Presenting seven detailed case studies through a common comparative framework by leading experts on French gender policy, it sheds light on if, how, and under what conditions gender equality policy in practice leads to success, overall gender transformation, and enhanced gender equality in democratic settings. The book contributes to ongoing comparative research that focuses on the post-adoption phases of implementation and evaluation and seeks to develop accurate recipes for gender equality policy success. It will appeal to all those interested in gender studies, comparative politics and public policy, and policy implementation. Isabelle Engeli is a Professor of Public Policy at the University of Exeter, UK. Amy G. Mazur is Claudius O. and Mary W. Johnson Distinguished Professor in Political Science at Washington State University, USA and Associate Researcher at LIEPP, Sciences Po Paris.